Enhancing EFL Students’ Writing Skill through LSP (Learn Social Platform): A Case of Indonesian Students - Arimuliani Ahmad; Estika Satriani; Fauzul Etfita; Alber Alber (INTERNATIONAL JOURNAL OF LANGUAGE PEDAGOGY, 2021)
In the industry revolution 4.0 era, the Indonesian government also strives to socialize the education change to increase the quality and effort to build up the students of higher education learning style more autonomously. One of many ways to be increased is e-learning. This research aimed to explore the effectiveness of using Learn Social Platform toward students’ writing skills and explore students’ perspectives of using this platform in one of the private universities in Riau, Indonesia. This research was a mixed-method approach. There are 38 undergraduate students as a sample of this research. To collect the data, the researcher used two kinds of instruments such as writing test for analyzing quantitative data and interview for qualitative data. The result showed that the use of this platform can give a significant effect on students’ writing skill which was revealed by students’ post-test was higher than pre-test. In addition, interview data reveal that students felt enthusiastic to use this platform because it is very helpful to increase their English skills which complete material and tasks. Even though it gave advantages, they also face some difficulties such as internet connection and limitation of study group enrollment. Then, the students have some advantages to be improved for this platform such as additional video conference, additional aspects of test, not only focus on grammar, vocabulary and language use but also reading, speaking, writing, and listening. In a practical case, the students expected to get feedback as soon as possible on the same day from their lecturer.